An efficient protocol for the synthesis of quinoxaline derivatives at room temperature using recyclable alumina-supported heteropolyoxometalates - Ruiz, Diego Manuel (2012)
We report a suitable quinoxaline synthesis using molybdophosphovanadates supported on commercial alumina cylinders as catalysts. These catalysts were prepared by incipient wetness impregnation. The catalytic test was performed under different reaction conditions in order to know the performance of the synthesized catalysts. The method shows high yields of quinoxaline derivatives under heterogeneous conditions. Quinoxaline formation was obtained using benzyl, o-phenylenediamine, and toluene as reaction solvent at room temperature. The CuH2PMo11VO40 supported on alumina showed higher activity in the tested reaction. Finally, various quinoxalines were prepared under mild conditions and with excellent yields.